Temporal Features of the Differentiation between Self-Name and Religious Leader Name among Christians: An ERP Study - Xia, Ruixue; Jin, Ruijie; Yong, Lin; Li, Shaodong; Li, Shifeng; Zhou, Aibao (Frontiers in Psychology, 2018)
Existing neuroimaging studies have shown that religion, as a subjective culture, can influence self-referential processing. However, the time course of this impact remains unclear. The present study examined how Christians process their own names, the name of their religious leader (i.e. Jesus), and a famous person’s name (i.e. Yao Ming). Behavioural and EEG data were recorded while the participants performed a name-colour judgement task for these three names. The behavioural data showed no significant differences in reaction time or accuracy among the names. However, the ERP data showed that the P200 and P300 amplitudes elicited by the self-name and religious leader name were larger than those elicited by the famous name. Furthermore, the self-name also elicited a larger P300 amplitude than the religious leader name did. These results suggested that both the self-name and the religious leader name were processed preferentially due to their important social value for the self as compared to a generally famous name. Importantly, the dissociation between the self-name and the religious leader name was observed at a high-order cognitive stage, which might be attributed to their different roles in one’s self-concept.